Fire resistance of corroded high-strength structural concrete. (17th September 2020) - Sobhan, Khaled; Reddy, Dronnadula V.; Martinez, Fernando
Abstract : Purpose: The exposure of reinforced concrete structures such as high-rise residential buildings, bridges and piers to saline environments, including exposure to de-icing salts, increases their susceptibility to corrosion of the reinforcing steel. The exposure to fire can further deteriorate the structural integrity of corroded concrete structures. This combined effect of corrosion damage and fire exposure is not generally addressed in the structural concrete design codes. The synergistic combination of the effects of corrosion and fire forms the basis of this paper. Design/methodology/approach: Concrete beam specimens with different strengths were prepared, moist-cured and corroded with impressed current. Later, they were "crack-scored" for corrosion evaluation, after which half were exposed to fire in a gas kiln. The fire damage was evaluated by nondestructive testing using ultrasonic pulse velocity. Next, all specimens were tested for residual flexural strength. They were then autopsied, and the level of corrosion was determined based on mass loss of the reinforcement. Findings: For corroded specimens, the flexural capacity loss because of fire exposure increases as the compressive strength increases. In general, the higher the crack score, the higher the corresponding mass loss, unless some partial/segmental debonding of the reinforcement occurred. The degree of corrosion increases with decreasing compressive strength. The residual moment capacity, based on analytically determined capacities of uncorroded and nonfire-exposed beams, was significantly lower than those of uncorroded beams exposed to fire. Originality/value: The combined effects of corrosion and fire on the mechanical properties of structural concrete are relatively unknown, and no guidance is available in the existing design codes to address this issue. Accordingly, the findings of the paper are expected to be valuable to both researchers and design engineers and can be regarded as the initial investigation on this topic.